INTELLECTUAL CAPITAL PADA ORGANISASI ISLAM DAN PERAN AKUNTANSI DALAM PERTANGGUNGJAWABAN KEPADA STAKEHOLDER - Nurizza Arsyi Isnaini; Akhmad Riduwan; Nur Fadjrih Asyik (Unitri Press, 2019)
The purpose of this research to determine the meaning and form of Intellectual Capital in Yayasan Masjid Al Falah Surabaya and the role of accounting in accountability to stakeholders. The method used is qualitative by interviewing 5 informants from internal and external parties. The results of the study reveal that human capital is one of the important components of Intellectual Capital because there are morals and faith; and found a new element of Intellectual Capital named mardhotillah capital which is the attitude of expecting Allah’s pleasure. Management accounting and financial accounting play a role in accountability to stakeholders.